Studies on influence of rapeseed vegetation stages on level of phenolic compounds - Siger Aleksander; Nogala Kalucka Malgorzata (Journal of Oilseed Brassica, 2026)
A study was conducted to evaluate the changes in native antioxidants in rapeseed (Brassica napus L),which take place during crop growth. During the growth, in anatomical parts of plants (Kana and Spencervarieties), the increased content of hydrophilic antioxidants (phenolic compounds) was observed. Duringthe plant maturation the decrease of phenolic acids was observed both in leaves during blooming and inhulls. During that time, total phenolic acid content decreased by 50% in Kana and by 40% in Spencer. Theprofile of phenolic acids in sampled rapeseed varieties was characterized by the highest level of sinapicacid and its low molecular derivative. It was proved, that during successive stages of maturation, the contentof phenolic acids varied in anatomical parts of the plant. This may suggest different biological functions ofparticular phenolic compounds.